CD8+ tumor‐infiltrating lymphocytes contribute to spontaneous "healing" in HER2‐positive ductal carcinoma in situ. (6th April 2016) - Morita, Michi; Yamaguchi, Rin; Tanaka, Maki; Tse, Gary M.; Yamaguchi, Miki; Kanomata, Naoki; Naito, Yoshiki; Akiba, Jun; Hattori, Satoshi; Minami, Shigeki; Eguchi, Susumu; Yano, Hirohisa
Abstract: We evaluated the associations between tumor‐infiltrating lymphocytes (TIL) including CD8‐positive [+] lymphocytes in ductal carcinoma in situ (DCIS) and histopathologic factors, particularly spontaneous "healing" and immunohistochemical (IHC)‐based subtypes, to clarify the effects of host immune response to cancer cells proliferation during early carcinogenesis for the breast cancer. This cohort enrolled 82 DCIS patients. We examined the relationships between clinicopathologic factors including age, DCIS architecture, Van Nuys classification, grade, comedo necrosis, apocrine features, TIL, CD8 + lymphocytes, healing, estrogen receptor and HER2 positivity, and IHC‐based subtypes [luminal, luminal‐HER2, HER2‐positive, triple negative (TN)]. The results were analyzed by univariate and multivariate analyses. High numbers of TIL (high‐TIL) and healing were seen in 30.5% and 39.0% of the cohort, respectively. The distributions of luminal, luminal‐HER2, HER2 and TN subtypes were 73.2%, 9.8%, 13.4%, and 3.6%, respectively. High Van Nuys grading, high‐grade, comedo necrosis, apocrine features, high‐TIL, high CD8 + lymphocytes and healing were significantly associated with HER2‐positive (luminal‐HER2, HER2), and TN subtypes. High‐TIL was significantly associated with high‐grade, comedo necrosis, apocrine features, healing, high CD8 + lymphocytes and HER2 and TN subtypes. Healing was significantly correlated with high CD8 + lymphocytes, high‐grade, comedo necrosis, apocrine features, and HER2‐positive and TN subtypes. Logistic regression analysis revealed a strong association between healing and TIL (odds ratio: 11.72, P  = 0.024). High CD8 + lymphocytes was also significantly associated with healing (odds ratio: 9.26, P  = 0.009). The results of this study suggested that the spontaneous healing phenomenon might be induced by CD8 + high‐TIL associated with high‐grade, comedo necrosis, apocrine features and HER2‐positive DCIS. Abstract : We evaluated the spontaneous "healing" phenomenon in ductal carcinoma in situ (DCIS) and its association with tumor‐infiltrating lymphocytes (TIL) including CD8 positive lymphocytes. Spontaneous "healing" may be attributable to CD8 + high‐TIL associated with high ‐grade, comedo necrosis, apocrine features, and HER2‐positive DCIS.